The Best Iron Chelation Therapy in Major Thalassemia Patients is Combination of Desferrioxamine and Deferiprone - Ebrahim miri moghaddam; Mohammad Naderi; Mohammad Ali Mashhadi; Ali Reza Rezvani (International Journal of Hematology-Oncology and Stem Cell Research, 2011)
Introduction: The best and effective iron chelation remain one of the major strategy in clinical management of thalassemia major patients. The purpose of this study was to evaluate the safety and effectiveness of combined therapy with Desferrioxamine and Deferiprone in patients with thalassemia major that undergoing in regular administration of adequate desferrioxamine (5-6 days/week). Patients and Methods: This study was performed in two groups: one group with combination therapy, that had received oral deferiprone 70 mg/kg /day for 6 days and two days desferrioxamine 40 mg/kg with subcutaneous injection. Other group treated with only desferrioxamine with doses of 40 mg/kg 5- 6 day/week resemble to one year ago. (In past year both groups had regular & adequate administration and consumption of desferrioxamine with doses of 40 mg/kg 5-6 day/week). Thirty six patients were entered in this study. The efficacy of combined therapy was evaluated in 19 patients that treated with Desferrioxamine and deferiprone and 17 patients that treated with Desferal alone for at least 12 month. In both group the patients were received Desferal in Regular program in one year ago until to start of this study. Age of the patients was over 10 years old. Deferiprone administered orally 70 mg/kg/day in three divided dose and desferrioxamine 40 mg/kg/day by subcutaneus infusion overnight for 8-12 hr twice weekly. Serum ferritin concentrations were measured at base, 6 and 12 month. Full blood count were performed every 15 day for 2 first months and then monthly. The evaluation of cardiac function was performed in regular manner (every 6 months) and all of patients had normal cardiac function. Results: The mean decreased of ferritin level was 493 μg/L in combination therapy and mean increased in ferritin level was 637.6 μg/L in desferrioxamine group. Statistical analysis was performed with using T-test, and Paired T-test. There were significant differences between the two groups (p-value= 0.0001). The most common side effects in combined therapy group were dyspepsia and nausea in 6 patients (18.1%), especially in the first month of treatment. Joint pain and stiffness were observed in 4 cases (13.6%). Significant neutropenia and agranulocytosis were not observed. The serum ferritin level was increased in 64.7 % of patients that treated with desferrioxamine alone. Conclusion: The results of this study confirmed that the thalassemia major patients with iron overloaded whom received desferrioxamine as a regular manner (at least 40 mg/kg for 5 days /week) can be safety treated with a combination of deferiprone and desferrioxamine. This combination therapy was effective in reducing iron burden, as assessed by serum ferritin level.